Current Population Survey: Annual Social and Economic (ASEC) Supplement Survey, United States, 2017 ([Verlag nicht ermittelbar], 2018)
The Annual Social and Economic (ASEC) 2017 Supplement is part of the Current Population Survey (CPS) Series. The CPS is a source of the official Government statistics on employment and unemployment. The Census Bureau conducts the ASEC (known as the Annual Demographic File prior to 2003) over a three-month period, in February, March, and April, with most of the data collected in the month of March. The ASEC uses two sets of survey questions, the basic CPS and a set of supplemental questions. The CPS, administered monthly, is a labor force survey providing current estimates of the economic status and activities of the population of the United States. Specifically, the CPS provides estimates of total employment (both farm and nonfarm), nonfarm self-employed persons, domestics, and unpaid helpers in nonfarm family enterprises, wage, and salaried employees, and estimates of total unemployment. In addition to the basic CPS questions, respondents were asked questions from the ASEC, which provides supplemental data on poverty, geographic mobility/migration, and work experience. Comprehensive work experience information was given on the employment status, occupation, and industry of persons aged 15 and over. Additional data for persons aged 15 and older were available concerning weeks worked and hours per week worked, reason not working full-time, total income and supplemental income components. Demographic variables include age, sex, race, Hispanic origin, marital status, veteran status, educational attainment, occupation, and income. Data on employment and income refer to the previous calendar year, although demographic data refer to the time of the survey. The occupation and industry information variables in this data collection can help the data users identify individuals who worked in arts and culture related fields. The occupations are listed in a category entitled "Arts, Design, Entertainment, Sports, and Media Occupations," which includes professions such as artists, designers, actors, musicians, and writers (see Appendix B of the User Guide for further category details). Industries related to the arts and culture are in the "Arts, Entertainment, and Recreation" category (see Appendix C of the User Guide for further category details). For example, using the occupation and industry information variables from the ASEC help data users to obtain statistics about people in artists occupations that receive supplemental income, live public housing, or are full-time students. The ASEC data provided by the Census Bureau are distributed in a hierarchical file structure, with three record types present: Household, Family, and Person. The ASEC is designed to be a multistage stratified sample of housing units, where the hierarchical file structure can be thought of as a person within a family within a household unit. Here the main unit of analysis is the household unit.